Promoting Academic Honesty in Public Universities: A Constructivist Approach - Ansari, Marium; Ghani, Sajida; Ullah, Shamim (Annals of Human and Social Sciences, 2023)
The constructivist perspective asserts that the acquisition of knowledge is a cognitive process centered on the creation of significance; it pertains to the manner in which individuals comprehend and interpret their encounters. Constructivism is the combination of numerous theories in one form. This study investigated the methods employed by students to engage in misconduct during online examinations. Under the topology of interpretivism qualitative research method was employed. The method of the research was phenomenology. Interviews with students provided insights into their perceptions of the online teaching-learning process. Students expressed concerns about the confusion generated by the online teaching-learning policy implemented. They highlighted their lack of technological expertise and perceived shortcomings of the online teaching policy, which created opportunities for student misconduct. Additionally, the formative and summative assessment methods were deemed inadequate. Some students also identified loopholes in the system that hindered effective learning.